Identifying the potential of transcription factor Sox9 gene transfer in chondrocytes differentiation and articular cartilage formation in vitro - Mohamad Sukri, Norhamiza; Ahmad Radzi, Muhammad Aa’zamuddin; Abdul Rahman, Rozlin; Zulkifly, Ahmad Hafiz; Abdulahi Hashi, Abdurezak; Sha'ban, Munirah (Universiti Teknologi Malaysia, 2015)
Sox9 plays an important role as transcription factor for chondrogenesis; the formation of cartilage. This study aimed to identify the potential of the transiently overexpressed Sox9 gene in human chondrocytes differentiation and tissue engineered cartilage (TEC) formation in vitro. Articular cartilage samples were obtained from osteoarthritic patients who underwent joint replacement surgery. The isolated chondrocytes were cultured and transfected with pcDNA3-Sox9 using lipofection technique. The TEC constructs were formed by incorporating the transfected and the non-transfected cells onto poly(lactic-co-glycolic acid) (PLGA) scaffold with or without fibrin. This approach allows a comparison between four groups i.e. (1) transfected chondrocytes seeded on PLGA/fibrin [PFTC], (2) non-transfected chondrocytes on PLGA/fibrin [PFC], (3) transfected chondrocytes on PLGA [PTC] and (4) non-transfected chondrocytes on PLGA [PC]. All TEC constructs were cultured and evaluated at each time point of 1, 2 and 3 weeks in vitro. All TEC constructs were analysed for gross observation, histology, immunohistochemistry, cell proliferation activity, gene expression and sulphated glycosaminoglycan (sGAG) production assay. After 3 weeks, all PFTC and PFC showed higher cell viability, higher sGAG content, better histological features and distribution of extracellular matrix in concert with positive glycosaminoglycan (GAG) accumulation when compared to the PTC and PC. However, at week 3, the PFC and PC exhibited significantly higher sGAG production than PFTC and PTC. Chondrogenic properties of the constructs were evidenced by the expression of cartilage-specific markers; collagen II, collagen XI and aggrecan core protein. In this study, due to the nature of a new cartilage formation, the co-expression of collagen I in all constructs can be an indication of early cartilage development. Based on the outcomes, it is hoped that this study will provide a good ground for future tissue engineering application.